Turning their Pain to Gain: Charismatic Leader Influence on Follower Stress Appraisal and Job Performance - LePine, Marcie A.; Zhang, Yiwen; Crawford, Eean R.; Rich, Bruce Louis (Academy of Management Journal, 2016)
We develop and test a theoretical model that explores how individuals appraise different types of stressful job demands and how these cognitive appraisals impact job performance. The model also explores how charismatic leaders influence such appraisal and reaction processes, and, by virtue of these effects, how leaders can influence the impact of stressful demands on their followers’ job performance. In Study 1 (n = 74 U.S. Marines), our model was largely supported in hierarchical linear modeling analyses. Marines whose leaders were judged by superiors to exhibit charismatic leader behaviors appraised challenge stressors as being more challenging, and were more likely to respond to this appraisal with higher performance. Although charismatic leader behaviors did not influence how hindrance stressors were appraised, they negated the strong negative effect of hindrance appraisals on job performance. In Study 2 (n = 270 U.S. Marines), charismatic leader behaviors were measured through the eyes of the focal Marines, and the interactions found in Study 1 were replicated. Results from multilevel structural equation modeling analyses also indicate that charismatic leader behaviors moderate both the mediating role of challenge appraisals in transmitting the effect of challenge stressors to job performance and the mediating role of hindrance appraisals in transmitting the effect of hindrance stressors to job performance. Implications of our results to theory and practice are discussed.